Household livelihoods in semi-arid regions: options and constraints - Campbell, Bruce M.; Jeffrey, S.; Kozanayi, W.; Luckert, M.; Mutamba, M.; Zindi, C. (Center for International Forestry Research, 2002)
The overall aim of this study was to explore what the development community can do, or facilitate, to significantly improve livelihoods in semi-arid systems.The authors based their analysis on two case-study sites in the communal lands of southern Zimbabwe. The main tool was a detailed livelihood questionnaire, supplemented by participatory appraisal and observation, action research, biophysical analysis and systems modelling. Most households rely on cash and subsistence income from a number of sources - dryland crop production, gardening, livestock production, woodland activities, wage or home industries and remittances/gifts. Marked wealth differentiation occurs, with local people recognising the different wealth groupings largely on the basis of various capital assets. One factor driving differentiation is whether a household has access to remittance income. Elements of change can be identified in numerous aspects of the capital assets and the livelihood strategies. The authors suggest that there are some key drivers of change, namely: (a) rainfall, (b) macro-economic changes, (c) changing institutional arrangements and social processes, and (d) demographic processes and HIV/AIDS. The overall conclusion is that there are very few options for significantly improving livelihoods in semi-arid regions and that the poverty alleviation targets set by the international community are overly ambitious.The analyses suggest that rainfall variation and the state of the macro-economy are likely to have a greater impact on livelihood status than local rural development interventions.